The Northern Irish hunger strikers as cultural icons - Erja Simuna (Akademisk Kvarter, 2015)
The aim of this article is to discuss hunger strikers as cultural icons. Fasting is a non-violent way of communicating a message or achieving a goal. It is a process that includes and reveals poignant cultural values, and can be regarded as a symbolic gesture. It is also a phenomenon recognised by many cultures. As the nature of this recognition can vary between different cultures, wider cross-cultural aspects of iconicity can be reached.